Aktivitas Antioksidan Ekstrak Metanol Daun Alpukat Menggunakan Metode DPPH - Alfin Surya; Zaiyar Nazir; Anggun Syazulfa (LPPM Universitas Muhammadiyah Riau, 2021)
Free radicals are molecules that lose electrons in their outer orbitals so that the number of electrons becomes odd and unstable. Free radicals can damage various macromolecule cells including proteins, carbohydrates, fats. Antioxidants are compounds that can donate one or more electrons to free radicals. Avocado leaves contain high bioactive components that can be used as a source of natural antioxidants. Avocado leaves that have been dried, mashed and then shifted with methanol. The extracts were tested by phytochemical screening, including flavonpoid, phenolic, tannin and antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhidrazyl) method. This method is based on the reduction of 2,2-diphenyl-1-picrylhydrazyl (DPPH) against free radicals which causes a change from purple to yellow 2,2-diphenyl-1-picrylhydrazyl) (DPPH). From the research, the IC50 values ​​in avocado leaves were 118.8056 µg / mL and 7,276 µg / mL on ascorbic acid as a positive control. From the IC50 value obtained, it is known that the methanol extract of avocado leaves has strong antioxidant activity to fight free radicals.